Yeasts from the Maritime Antarctic: tools for industry and bioremediation - Bezus, Brenda; Garmendia, Gabriela; Vero, Silvana; Cavalitto, Sebastian Fernando; Cavello, Ivana Alejandra (Antarctic Science)
We isolated 32 yeasts from King George Island, which we then identified and characterized. Twenty-six belonged to Basidiomycota among the genera Naganishia, Holtermaniella, Vishniacozyma, Phenoliferia, Mrakia and Cystobasidium, and only six were Ascomycota of the genera Metschnikowia and Debaryomyces. Thirteen were psychrophiles, while 19 were psychrotolerant. Certain isolates exhibited a high tolerance to NaCl (3.5 M), while most tolerated Ni2+, Zn2+ and Li+. Cu2+ and Cd2+, however, inhibited the growth of most of the isolates. We assessed a bioprospecting of extracellular enzymes and their ability to biodegrade or bioaccumulate textile dyes. β-Glucosidases (59%) and esterases (53%) were the main extracellular enzymes detected. A minor proportion of the yeasts produced pectinases and xylanases; only psychrophiles produced proteases. Vishniacozyma, Naganishia, Phenoliferia and Mrakia were the richest genera in terms of enzyme production. Greater than 70% of the isolates decolourized solid medium supplemented with various dyes at 4°C and 20°C. Isolates belonging to the genera Vishniacozyma, Cystobasidium, Mrakia and Phenoliferia seem to have potential for textile dye bio-decolourization. The results demonstrated that yeasts collected from the Maritime Antarctic are a potential source of new enzymes of biotechnological interest, and that certain isolates could potentially be considered in the design of textile wastewater decolourizations. Fil: Bezus, Brenda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Garmendia, Gabriela. Universidad de la República. Facultad de Química; Uruguay Fil: Vero, Silvana. Universidad de la República. Facultad de Química; Uruguay Fil: Cavalitto, Sebastian Fernando. Consejo Nacional de Investigaciones ...